2009
DOI: 10.1097/sla.0b013e318195e164
|View full text |Cite
|
Sign up to set email alerts
|

Extended Liver Resection for Intrahepatic Cholangiocarcinoma

Abstract: Extended resections for IHC resulted in a favorable rate of R0-resection, which is the most important prognostic variable. Staging of IHC according to sixth edition of the TNM classification is superior in comparison with the fifth edition as indicated by the results of the multivariate analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(18 citation statements)
references
References 29 publications
0
17
1
Order By: Relevance
“…Despite an improved trend in the prognosis of patients with BTC subjected to surgical resection [11,12], the 5-year survival rate has remained approximately 25–30% for successful resection cases [13]. Some investigators have used a more aggressive approach to achieve R0 resection, even in patients with regional lymph node involvement [14]. The value of systematic lymphadenectomy has not been adequately proven to date.…”
Section: Discussionmentioning
confidence: 99%
“…Despite an improved trend in the prognosis of patients with BTC subjected to surgical resection [11,12], the 5-year survival rate has remained approximately 25–30% for successful resection cases [13]. Some investigators have used a more aggressive approach to achieve R0 resection, even in patients with regional lymph node involvement [14]. The value of systematic lymphadenectomy has not been adequately proven to date.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] Based on its anatomical location, ICC constitutes one of the three categories of cholangiocarcinoma (intrahepatic, hilar, and extrahepatic). As a poorly understood variant of cholangiocarcinoma, ICC has been considered to be the least common category among the above 3 from a histological point of view.…”
Section: Introductionmentioning
confidence: 99%
“…Studies about the efficacy of liver resection in patients with IHC showed long-term survival rates ranging from 30−60 % at 5 years after resection [1517]. Even in the presence of a more advanced tumor stage, partial hepatectomy can provide long-term survival in a considerable share of patients and the growing experience in liver surgery facilitates extended hepatectomies and provides a chance of cure in formerly non-resectable liver malignancies [15]. The published results of large series of patients who received liver resection within the last 2 years underlined not only the therapeutic efficacy of this treatment but also its safety.…”
Section: Discussionmentioning
confidence: 99%